Common Fixed Points of Generalized Cyclic Meir-Keeler-Type Contractions in Partially Ordered Metric Spaces - Chiming Chen; Ing-Jer Lin (Abstract and Applied Analysis)
The purpose of this paper is to prove some common point theorems for the generalized cyclic Meir-Keeler-type ()-contraction in partially ordered metric spaces. Our results generalize many recent common point theorems in the literature.